2013
DOI: 10.1002/adma.201301679
|View full text |Cite
|
Sign up to set email alerts
|

Color Manipulation of Mechanoluminescence from Stress‐Activated Composite Films

Abstract: The prospective application of luminescence to imaging devices is shown using a combination of color-tunable and patternable mechanoluminescent materials. A white light source is demonstrated by using an alternative color tuning method, induced under high vibration conditions. As the implementation is fairly straightforward, it is expected that the present results will find a number of potential uses in current industrial applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
167
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 231 publications
(168 citation statements)
references
References 27 publications
1
167
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10]. Jeong et al [8][9][10] have demonstrated that the composite film containing ZnS:Cu, Mn and ZnS:Cu phosphors in a polydimethylsiloxane (PDMS) matrix can be used to produce light source, multicolour displays, and wind-driven light sources.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10]. Jeong et al [8][9][10] have demonstrated that the composite film containing ZnS:Cu, Mn and ZnS:Cu phosphors in a polydimethylsiloxane (PDMS) matrix can be used to produce light source, multicolour displays, and wind-driven light sources.…”
Section: Introductionmentioning
confidence: 99%
“…Beside the persistent luminescence properties, LPLMs are reported to exhibit mechanoluminescence and photo-stimulated up-conversion (PSUC) properties [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The widely studied elasticomechanoluminescent materials known to date are as follows [4][5][6]: show such an intense EML that it can be seen in daylight with naked eye. The elastico ML has potential for sensing [7,8], imaging [6,9], multicolour light sources and multicolour displays [10][11][12].…”
Section: Introductionmentioning
confidence: 99%